Age, gender, and regional variations in stroke epidemiology in India: A systematic review and meta-analysis - Jaison Joseph; Biji P. Varkey; Abin Varghese; Elezebeth Mathews; Manju Dhandapani; Suresh K. Sharma; Saleena Shah; Venkata Lakshmi Narasimha; Vishnu Renjith; Sivashanmugam Dhandapani; G. B. Manjula (Wolters Kluwer Medknow Publications, 2024)
Introduction: There is a wide variation in stroke epidemiology in India due to the differences in culture and the variability in the distribution of risk factors across the states. The present meta-analysis provides a pooled estimate of age, gender, and region-based stroke epidemiology in India based on epidemiological transition level (ETL) groups described in the Global Burden of Disease (GBD) Study (2016). Methods: We searched in PubMed and Google Scholar, and relevant studies published till February 2022 were included. Observational studies conducted in the Indian setting were included and global or Indian studies that exclusively estimated the prevalence, incidence, or mortality data among patients with stroke were excluded. The Joanna Briggs Institute (JBI) Critical Appraisal Checklist was used for the risk-of-bias assessment and publication bias was evaluated by funnel plots and Egger's test. The R software was used to perform this meta-analysis; I2 statistics were calculated to measure heterogeneity among studies. Results: We included 58 studies in the systematic review, and after quality assessment, 47 studies were finally included for meta-analysis. The sample sizes of the included studies ranged from 40 to 4989 and the mean age of the participants ranged from 31.7 (Standard Deviation, SD-7.4) to 70.5 (SD-10.7). The burden of stroke was estimated based on the ETL groups described in the GBD Study 2016. We found a male preponderance (64.5%; 95% confidence interval [CI]: 62.5%-68.3%) in the gender distribution of strokes and 75.2% (95% CI: 68.7%-81.7%) of the stroke occurred above the age of 50 years. Ischemic stroke is the predominant subtype of stroke in India, with a higher proportion in the middle ETL region (74.0%; 95% CI: 65.1%-81.3%) as compared to those with low ETL (67.2%; 95% CI: 49.9%-80.8%) and high ETL regions (67.5%; 95% CI: 57.0%-76.4%). Conclusion: There was a significant heterogeneity among the included studies. Majority of strokes occurred in the age group of more than 50 years with a male preponderance. Ischemic stroke was the most common type of stroke with its proportion varying from 67% to 74% depending on ETL. PROSPERO Registration: CRD42022316774.